Experimental investigation of gas turbine compressor water injection for NOx emission reductions - Block novelo, David alejandro; Igie, Uyioghosa; Szymański, Artur (Elsevier, 2019)
The global rising demand for civil air travel shows good prospects for the industry, however, this growth is inevitably matched with higher levels of emissions and fuel consumption. In this study, demineralised water injection is presented as an alternative to reduce NOx emissions and enhance engine performance. The experimental study firstly presents the droplet size characterisation of a spray nozzle. This is done for varied injection pressure, water temperature and at varied axial and radial locations using an impaction pin nozzle. The single-shaft Artouste engine is used in conducting the compressor water injection test with water-to-air ratios of 0.5, 1 and 2%. The water droplet diameter, engine gas path and exhaust emissions are all monitored in real time. For the engine tests, droplets are measured at the spraying point and correlations are used to account for the droplet size at the inlet of the compressor due to measurement difficulties in this region. The test showed a reduction in compressor discharge temperature by up to 34 K and a NOx decrease by 25%. Nevertheless, the higher reductions in NOx at higher water-to-air ratios are attributed to a predominant cooling in the combustor because of unevaporated water in the compressor. At 0.5% water-to-air ratio, the drop in NOx is mainly due to compressor cooling and signified by the only case in which the fuel-to-air ratio reduces. The study presents evidence of the combined effects of compressor and combustor water ingestion. The CO is seen to increase significantly and associated with reduced combustor efficiency.
Keywords: Water injection; Engine experiment; Compressor; Combustor; NOx